PERBEDAAN PENGGUNAAN MODEL PBL DENGAN PROBLEM POSING TERHADAP HASIL BELAJAR SKALA DI SEKOLAH DASAR - Rahmi, Aulia; Masniladevi, Masniladevi; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This reseach aims at finding out a significant difference of students learning outcomes of the scale between the PBL and Problem Posing Models of learning outcomes Scale in the Plan in class V SD Group 1 Payakumbuh City. This type of research is an experiment using a quasi-experimental design in the form of a pretest-posttest non-equivalent group. The samples were students of class VA and VB of SDN 28 Payakumbuh. The research sample was 40 students selected based on cluster random sampling technique. The instrument used in collecting data is a test with a description form. Based on the t-test of the students post-test scores, it was found that tcount 2,08> ttable 2,02 α 0,05. It means the PBL model is a better compared to the Problem Posing model class V SD Group 1 Payakumbuh City.Keywords: PBL, Problem Posing, sclae learning outcomes.